2018
DOI: 10.1038/s41598-018-21034-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermally-Conductive and Mechanically-Robust Graphene Nanoplatelet Reinforced UO2 Composite Nuclear Fuels

Abstract: Low thermal transport behavior along the radial direction of nuclear fuel pellets and pellet-cladding mechanical interaction significantly impact fuel performance and the safety of current nuclear energy systems. Here we report a new strategy of advanced fuel design in which highly thermally-conductive and mechanically-robust graphene nanoplatelets are incorporated into UO2 fuel matrix to improve fuel thermal-mechanical properties. The 2D geometry of the graphene nanoplatelets enables a unique lamellar structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 38 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The pellet preparation experiment was carried out for the mixed powders prepared by in situ synthesis. The procedure was as follows: the appropriate quantityUO 2 -graphene mixed powder was weighed into a graphite mold and sintered for 1 h at 1723 K and 60 MPa to yield UO 2 -graphene composite fuel sintered pellets [8,14].…”
Section: Preparation Of Uo 2 -Graphene Composite Fuel Pelletsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pellet preparation experiment was carried out for the mixed powders prepared by in situ synthesis. The procedure was as follows: the appropriate quantityUO 2 -graphene mixed powder was weighed into a graphite mold and sintered for 1 h at 1723 K and 60 MPa to yield UO 2 -graphene composite fuel sintered pellets [8,14].…”
Section: Preparation Of Uo 2 -Graphene Composite Fuel Pelletsmentioning
confidence: 99%
“…As a promising second-phase additive in UO 2 fuel pellets, graphene has a high melting point (~3773 K) and thermal conductivity (~3000 W/(m•K)) at room temperature, and is stable at high temperatures [8,9]. T. Yao et al reported highly thermally conductive and mechanically strong UO 2 -graphene composite fuels using a metallurgical approach; the composite fuels possessed greatly improved thermal conductivities (74% and 162 wt.% enhancement at room temperature along the radial direction for 1 wt.% and 5 wt.% graphene composites), and they observed 150% improvement in fracture toughness compared to UO 2 [8]. D. Zhang et al reported a hydrothermal approach to synthesize UO 2 and RGO sheets with an enhancement of approximately 35.4% in thermal conductivity [9].…”
Section: Introductionmentioning
confidence: 99%
“…The myriad of defect types and interactions in nuclear fuel under irradiation has motivated researchers to consider improving function by controlling defect evolution and structure. Examples include using dopants to control defect concentrations by modifying grain size [10,11,12,13], simulating HBS using nanocrystalline UO2 to improve fission gas retention and improve mechanical properties [14,15], and directly adding other materials to UO2 to raise the thermal conductivity [16,17,18,19,20,21,22,23,24]. Expediting progress towards tailoring defects and microstructure to bring about desired thermal properties will require further development of fundamental, predictive models of phonon transport in actinide oxide fuels containing irradiation-induced defects [25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is a 2D C nanomaterial with sp 2 hybridization that has a wide range of industrial applications, including the production of ion-selective graphene oxide (GO) membranes for desalination and salinity gradient energy, radioactive wastewater treatment, the production of heavy water, and others [1][2][3][4]. Generally, this material is used as graphene nanoplatelets (GNPs) due to the possibility of producing it directly from graphite in larger volumes at a lower cost.…”
Section: Introductionmentioning
confidence: 99%